Mineral supplementation on steers grazing fertilized guineagrass pasture - Sousa, Júlio César De; Gomes, Ronaldo F. Correia; Silva, José Marques da; Euclides, Valéria Pacheco B. (Pesquisa Agropecuaria Brasileira, 2014)
A study to verify possible effect of mineral supplementation on weight gain of Nelore steers grazing fertilized guineagrass pasture (Panicum maximum Jacq.) was conducted for 814 days in Miranda, West of the state of Mato Grosso do Sul, Brazíl. Fertilization was done with 250 kg of simple superphosphate and 250 kg/ha of hyperphosphate. Eighty steers in the following treatments of mineral supplementation were used: A: without mineral supplementation; B : NaCl; C : NaCl + P; and D: NaCl + P + microelements. Weight gain per animal were: 235.6, 278.8, 296.8 and 278.9 kg for the treatments A, B, C and D, respectively. During the dry season all animals lost weight, regardless of mineral supplementation. Biopsy of rib-bone showed low levels of Ca, P and also low percentage of bone ash in all treatments. Dry matter of forage was frequently deficient for the elements: P, Na and Zn. Soil level of Zn was low but other nutrients were at adequate levels. Economic analysis pointed out the superiority of treatment B.